2013
DOI: 10.3389/fonc.2013.00110
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Novel Targeted Molecular Agents and Radiation in the Treatment of Pediatric Gliomas

Abstract: Brain tumors are the most common solid pediatric malignancy. For high-grade, recurrent, or refractory pediatric brain tumors, radiation therapy (XRT) is an integral treatment modality. In the era of personalized cancer therapy, molecularly targeted agents have been designed to inhibit pathways critical to tumorigenesis. Our evolving knowledge of genetic aberrations in pediatric gliomas is being exploited with the use of specific targeted inhibitors. These agents are additionally being combined with XRT to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…BRAF inhibitors targeted to the mutant V600E protein have shown efficacy in inhibition of mutant cells in vitro (34) and in murine xenografts (33). Phase I trials for BRAF V600E inhibition are currently under way (83). Conversely, Sievert et al (35) showed that cells expressing KIAA1549-BRAF are resistant to vemurafenib (PLX4032; Plexxikon, Berkeley, CA), a small molecule inhibitor of BRAF V600E.…”
Section: Discussionmentioning
confidence: 99%
“…BRAF inhibitors targeted to the mutant V600E protein have shown efficacy in inhibition of mutant cells in vitro (34) and in murine xenografts (33). Phase I trials for BRAF V600E inhibition are currently under way (83). Conversely, Sievert et al (35) showed that cells expressing KIAA1549-BRAF are resistant to vemurafenib (PLX4032; Plexxikon, Berkeley, CA), a small molecule inhibitor of BRAF V600E.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted inhibitors with radiation are currently under investigation. 47 Aggressive surgery, if possible, has been associated with better survival of high-grade gliomas, although it is not clear whether this is owing to surgery alone or biological differences between tumors that can be ''totally'' resected and those that cannot. In the Children's Cancer Group (CCG) 945 clinical trial, children with high-grade glioma who underwent gross total resection had 5-year progression-free survival of 35%, compared to 17% for patients with subtotal resection.…”
Section: High-grade Gliomasmentioning
confidence: 99%
“…The serine/threonine kinase BRAF is a member of the RAS/RAF/MEK/ERK kinase pathway, which plays a key role in cellular division, survival and metabolism [53]. A missense mutation at amino acid position 600 of BRAF ( BRAF V600E ) leads to overactivation of the gene and, consequently, uncontrolled cell proliferation.…”
Section: Brafv600ementioning
confidence: 99%
“…A missense mutation at amino acid position 600 of BRAF ( BRAF V600E ) leads to overactivation of the gene and, consequently, uncontrolled cell proliferation. BRAF V600E was initially associated with melanoma and medullary thyroid carcinoma but later found in several types of low- and high-grade glial brain tumors [5355]. Among the low-grade gliomas in children, BRAF V600E was most frequently detected in pleomorphic xanthoastrocytomas (66%), followed by gangliogliomas (18%) and pilocytic astrocytoma (9%) [55].…”
Section: Brafv600ementioning
confidence: 99%